Pointing out the Dharmakaya of the Ninth Karm[a]pa Wangchug Dorje - Ka-rma-blo-gros (Bibliotheca Indo-Buddhica series, 2001)
On Mahamudra tantric practice according to Karma Bkaʾ-rgud-pa tradition of Tibet